2015
DOI: 10.1126/scitranslmed.aab3142
|View full text |Cite
|
Sign up to set email alerts
|

T H 2 and T H 17 inflammatory pathways are reciprocally regulated in asthma

Abstract: Concurrent blockade of IL-13 and IL-17A may improve control of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
364
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(400 citation statements)
references
References 62 publications
(108 reference statements)
26
364
2
8
Order By: Relevance
“…This finding suggests that Th2 activation precedes Th17 activation and not the reverse. Second, in asthma, it was recently demonstrated that there are 3 subgroups (i.e., Th2 high , Th17 high , and Th2 low /Th17 low ), but not a group with high expression of both Th2 and Th17, which shows that these cell types are mutually exclusive [47]. This result was explained by the experimental findings of Newcomb et al [45,46].…”
Section: Discussionmentioning
confidence: 91%
“…This finding suggests that Th2 activation precedes Th17 activation and not the reverse. Second, in asthma, it was recently demonstrated that there are 3 subgroups (i.e., Th2 high , Th17 high , and Th2 low /Th17 low ), but not a group with high expression of both Th2 and Th17, which shows that these cell types are mutually exclusive [47]. This result was explained by the experimental findings of Newcomb et al [45,46].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, CXCR2 signaling derived Th2 responses are enhanced. 118 In patients with CRS with NP IL-25 and IL-33 interact locally with IL-17RBþST2þ polyp T cells to augment Th2 responses. 115 IL-17 significantly increases MUC5B mucin expression, while IL-13 additionally induces significant goblet cell hyperplasia and MUC5AC mucin expression in CRS with NP.…”
Section: Neurogenic Inflammationmentioning
confidence: 99%
“…Neutralization of both IL-13 and IL-17 protected mice from eosinophilia, mucus hyperplasia, and airway hyperreactivity and abolished the neutrophilic inflammation, suggesting that combination therapies targeting both pathways may maximize therapeutic efficacy across a patient population with a mixed Th2/ Th17 endotype. 118 Chitinases and chitinase-like proteins (CLPs) may be an important link between type 2 immunity and IL-17. Acting as dangerassociated molecular patterns CLPs release IL-1 with IL-17 production by innate gd T cells, which in turn drives a type 2 response.…”
Section: Neurogenic Inflammationmentioning
confidence: 99%
“…Imbalances of Th17/Treg cells have been demonstrated in patients with allergic asthma, and were shown to be associated with moderate to severe asthma [12, 13]. Choy et al [14] have identified Th2-high, Th17-high, and Th2/–17-low 409 clusters of patients with asthma, and combination therapies targeting both Th2 and Th7 pathways could provide additional efficacy over single inhibition. In addition, the elevated plasma IL-17 and IL-22, as well as the circulating Th17 cells are important features of allergic asthma and the Th17-driven immunity is paralleled with the severity of asthma, as indicated by Zhao et al [15].…”
Section: Introductionmentioning
confidence: 99%